Evidence for Seed Transmission of Xylella fastidiosa in Pecan (Carya illinoinensis) - Cervantes, Kimberly; Hilton, Angelyn E.; Stamler, Rio A.; Heerema, Richard J.; Bock, Clive; Wang, Xinwang; Jo, Young-Ki; Grauke, L. J.; Randall, Jennifer J. (Frontiers in Plant Science, 2022)
Pecan bacterial leaf scorch (PBLS), caused by Xylella fastidiosa subsp. multiplex, is an economically significant disease of pecan with known detrimental effects on the yield of susceptible cultivars. In this study, endosperm was harvested from developing pecan seeds, and direct qPCR and sequencing were used to detect and confirm the presence of X. fastidiosa. DNA was isolated from mature seeds originating from seven trees, revealing a positivity rate up to 90%, and transmission of X. fastidiosa from infected seed to the germinated seedlings was found to be over 80%. Further epidemiological analyses were performed to determine where X. fastidiosa localizes in mature seed and seedlings. The highest concentrations of X. fastidiosa DNA were found in the hilum and outer integument of the seeds and the petioles, respectively. High-, medium-, and low-density seeds were harvested to determine the impact of the bacterium on seed density and seedling growth rate. The growth rate of seedlings originating from low-density seeds was significantly reduced compared to the medium- and high-density seeds. Despite the increased growth and germination rates, the high-density seed group had a greater proportion of samples that tested positive for the presence of X. fastidiosa by qPCR. The results demonstrate the ability of X. fastidiosa to colonize developing seeds and be efficiently transmitted from well-developed seeds to germinated seedlings. Continued research is needed to understand the plant-microbe interactions involved in the colonization of pecan seeds by X. fastidiosa and to develop effective phytosanitary approaches to reduce the risks posed by seed transmission.